2019
DOI: 10.3390/met9050588
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Validation of Sound Absorption Performance of 10-Layer Gradient Compressed Porous Metal

Abstract: Sound absorption performance of a porous metal can be improved by compression and optimal permutation, which is favorable to promote its application in noise reduction. The 10-layer gradient compressed porous metal was proposed to obtain optimal sound absorption performance. A theoretical model of the sound absorption coefficient of the multilayer gradient compressed porous metal was constructed according to the Johnson-Champoux-Allard model. Optimal parameters for the best sound absorption performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Based on the theoretical sound absorption model of the polyurethane foam in Section 2.1.1 and the experimental data obtained in the following measurement, identification of acoustic characteristic parameters of the polyurethane foam was achieved by the cuckoo search algorithm [24][25][26][27], and the calculation flow chart is shown in Figure 2. In this study, experimental data of sound absorption coefficients of the polyurethane foam with thicknesses of 20 mm, 30 mm, 40 mm, and 50 mm were measured and utilized in this identification process, and the detected frequency points were in the range of 100-6000 Hz with the interval of 100 Hz, which indicated that there were 240 groups of data (4 × 60 = 240).…”
Section: Identification Of Acoustic Characteristic Parameters Of the mentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the theoretical sound absorption model of the polyurethane foam in Section 2.1.1 and the experimental data obtained in the following measurement, identification of acoustic characteristic parameters of the polyurethane foam was achieved by the cuckoo search algorithm [24][25][26][27], and the calculation flow chart is shown in Figure 2. In this study, experimental data of sound absorption coefficients of the polyurethane foam with thicknesses of 20 mm, 30 mm, 40 mm, and 50 mm were measured and utilized in this identification process, and the detected frequency points were in the range of 100-6000 Hz with the interval of 100 Hz, which indicated that there were 240 groups of data (4 × 60 = 240).…”
Section: Identification Of Acoustic Characteristic Parameters Of the mentioning
confidence: 99%
“…Similar with the polyurethane foam, porous metal was another common porous material used in the field of sound absorption [8,17,22,27,29,33,35]. Besides common standard porous metal, some novel sound absorbers had been proposed, such as uniform compressed porous metal [35], gradient compressed porous metal [8,22,27], microperforated compressed porous metal panel [29], and so on. The horizontal comparisons of the actual average sound absorption coefficient of the optimal composite sound absorbing structure with that of other porous materials were conducted when total thickness was 20 mm, as shown in Table 5.…”
Section: Comparisons With the Other Porous Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Normally, no matter for the common porous metal or for composite sound-absorbing structure, the structural parameters must be optimized to achieve the satisfactory sound absorption performance under certain constraint conditions [16][17][18][19][20][21]. Acoustic topology optimization of porous material distribution based on the adjoint variable fast multipole boundary element method was conducted by Zhao et al [16], and its ability to handle the large-scale problems was validated through numerical examples of acoustic scattering over a single cylinder and multiple cylinders.…”
Section: Introductionmentioning
confidence: 99%